Catatonic features in children and adolescents with N-methyl-d-aspartate receptor antibody encephalitis. Issue 4 (July 2020) - Eyre, Michael; Kaushik, Anya; Barrett, Elizabeth; King, Mary D.; Pollak, Thomas; Dale, Russell C.; Byrne, Susan; Lim, Ming
Abstract : Catatonia is a psychomotor dysregulation syndrome of diverse aetiology, increasingly recognised as a prominent feature of N -methyl-d -aspartate receptor antibody encephalitis (NMDARE) in adults. No study to date has systematically assessed the prevalence and symptomatology of catatonia in children with NMDARE. We analysed 57 paediatric patients with NMDARE from the literature using the Bush-Francis Catatonia Rating Scale. Catatonia was common (occurring in 86% of patients), manifesting as complex clusters of positive and negative features within individual patients. It was both underrecognised and undertreated. Immunotherapy was the only effective intervention, highlighting the importance of prompt recognition and treatment of the underlying cause of catatonia.